Correction to: Methylation of ZNF331 is an independent prognostic marker of colorectal cancer and promotes colorectal cancer growth - Yuzhu Wang; Tao He; James G. Herman; Enqiang Linghu; Yunsheng Yang; François Fuks; Fuyou Zhou; Linjie Song; Mingzhou Guo (Clinical Epigenetics, 2018)
Abstract After publication of the original article [1], it came to the authors’ attention that a reference was omitted from the Background.